Dynamic Design Quality Evaluation of Power Enterprise Digital System Based on Fuzzy Information Axiom. (18th August 2022) - Wu, Xinping; Geng, Xinzhou; Chen, Zhiyi; Dong, Aidi; Li, Jinchao
Abstract : With the deepening of digital transformation and upgrading of power grid enterprises, the digital system evaluation method of power grid enterprises based on experts' subjective experience has been unable to meet the management needs of modern enterprises. In this paper, a method based on fuzzy information axiom for dynamic design quality evaluation of digital system in electric power enterprises is proposed. Firstly, the electric power enterprise digital system dynamic design quality comprehensive evaluation index system is set up from three aspects, which are achievement degree of target business function, logical relation rationality, and technical economy of physical model. Secondly, the quantitative and qualitative index values are processed by using the information calculation formula of minimum information axiom and fuzzy membership function. And then best-worst method and antientropy weight method are used to form the comprehensive evaluation model. Finally, the feasibility and effectiveness of the design scheme are verified by an example of dynamic design of digital system in power enterprise.